An automated mechanical endurance test equipment using programmable logic controller (PLC) for microwave oven door system / Muhammad Ulwi Hashim - Hashim, Muhammad Ulwi (1993)
This project is to design and develop A Mechanical Endurance Test Equipment using Programmable Logic Controller (PLC) and Pneumatic System. This endurance test equipment is used for testing of the microwave oven doors system. The microwave oven doors system must be tested to open and close at a maximum travel for 100,000 cycles continuously to ensure that they are safe and reliable to the consumers. The Mechanical Endurance Test Equipment using the concept that employ the combination of electrical and pneumatic system is developed. This system is intergrated with the used of PLC. The PLC is used to transmit and process the electrical signals. The software routine known as ladder diagram is developed. This software is used in the PLC to control the testing equipment.